Rhyme words in English love lyric 1300-1579 - Holton, A (University of Oxford, 2024)
This dataset includes information about the rhyme words and rhyme groups in c. 925 love lyrics written in English and printed or copied between 1300 and 1579. It was initially assembled in Filemaker between 2005 and 2008, transferred to a Booster database in 2010, and finally to Google Sheets in 2023. It was created to support research for a monograph, Rhyme and the Construction of Love in English Lyric 1300-1579, published by OUP.